Learning Management System Applying the KMSLC Method as a Visual Programming Learning Media - Hidayah, Debby Ummul; Lestari, Puji; Kasih, Dwifa Julieta (Sistemasi: Jurnal Sistem Informasi, 2024)
Students' lack of understanding when attending lectures can result in less than optimal learning outcomes. The increasingly rapid use of information technology is not an obstacle for students to improve their learning. However, the learning media used must be relevant and valid. In the sense that the learning media contains learning material that is appropriate to the course being taught and has reliable references. Therefore, media such as a learning management system or LMS can be an appropriate solution as a learning medium. In this study, researchers took samples from visual programming courses which the majority of students considered to be difficult courses. The visual programming course does not only contain theory but also has practicum, namely visual programming using the C# (C Sharp) language. With an LMS, the material can be more structured and in accordance with the semester learning plan. With this foundation, this research aims to design a learning management system based on the google site. The method used in this research refers to the KMSLC (knowledge management system life cycle) method which has 6 stages, namely evaluate existing infrastructure, form the KM team, knowledge capture, design KM blueprint, verify and validate KM system, and implement the KM system. The research results show that a google site-based LMS (learning management system) has been successfully designed to support visual programming courses. Based on testing using the black box testing method, this google site-based LMS was declared successful and can be used as a learning medium for visual programming courses.